Technological and Collaborative Dynamics in Online Autonomous Writing Among Indonesian EFL Learners - Aini S, Qurrotul; Kristina, Diah; Fauziati, Endang (VELES Voices of English Language Education Society, 2024)
In the digital age, autonomous learning has become a cornerstone of education, particularly in English as a Foreign Language (EFL) contexts, where writing autonomy plays a crucial role in fostering critical thinking, creativity, and effective communication. The rapid shift to online learning during the COVID-19 pandemic created new opportunities to enhance writing autonomy through technology and digital tools. However, the integration of these advancements remains limited in contexts like Indonesia, where traditional education models prevail. This qualitative case study investigates the factors influencing online autonomous writing among Indonesian EFL learners, focusing on five secondary school students who participated through structured interviews and reflective journals. Findings reveal that technology, such as grammar checkers and online platforms, significantly enhances writing accuracy and fosters learner autonomy, while teacher feedback is a crucial guide for improvement. Additionally, collaborative processes stimulate critical thinking and deeper engagement, creating dynamic environments conducive to autonomous learning. These insights underscore the transformative potential of digital tools and feedback mechanisms in supporting writing development. By addressing existing gaps in the literature, this study offers practical recommendations for educators and policymakers, emphasizing the importance of integrating digital tools effectively and providing robust teacher training in digital pedagogy to improve EFL writing outcomes in increasingly digitalized learning environments.